Assessment of liver fibrosis by acoustic radiation force impulse elastography in rheumatic disease patients on long-term methotrexate treatment - Arindam Nandy Roy; Gayatri Senapathy; Vijay Kumar Bongu; Yarram Ashok Kumar; Syeda Sana Fatima; Regina Lata Thadigiri (Indian Journal of Rheumatology)
Background: Methotrexate treatment has been associated with liver fibrosis in patients with rheumatic disease. Liver biopsy has been the gold standard for staging liver fibrosis. Acoustic Radiation Force Impulse (ARFI) imaging is a new accurate, non-invasive method for staging liver fibrosis. Till date, no study has been conducted to evaluate the diagnostic value of ARFI in patients with rheumatic disease undergoing methotrexate treatment. Study Objective: To assess the degree of liver fibrosis with non-invasive ARFI and to compare the findings with the biochemical parameters in rheumatic disease patients taking methotrexate for long duration. Study Method: We reviewed the medical records of rheumatoid arthritis patients who were administered methotrexate for more than 2 years. A total of 151 patients with rheumatic disease, aged ≥ 18 years were enrolled into the study. In addition, 24 healthy subjects (controls) were recruited to compare the ARFI values with that of patients with rheumatic disease. On the day of the ARFI examination, a series of biochemical parameters were also assessed in the patient group. Pre-defined cut-off ARFI values were used to assess the stage of liver disease. Results: The mean ARFI value in the patient group was 1.14. The mean ARFI values of different rheumatic disease patients were 1.13 (0.0), 1.26 (0.19), 1.16 (0.15), 0.945 (0.21) for Rhupus, rheumatoid arthritis, psoriatic arthritis and Sjogren's syndrome, respectively. Biochemical abnormalities (ALT/AST) were seen in 33 (21.85%) patients. Three patients had ARFI abnormalities (1: cirrhosis and 2: early stage fibrosis). There was no correlation between the ARFI values / biochemical parameters and the cumulative dose of methotrexate. However, the ARFI values correlated with the aspartate aminotransferase (AST), alanine aminotransferase (ALT) and AST to platelet ratio index. Liver fibrosis is rare in rheumatoid arthritis patients treated with a high cumulative dose of methotrexate, and is not accurately detected in patients with liver enzyme abnormalities. Conclusion: Considering the risk and benefit ratio of liver biopsy, ARFI may be a useful non- invasive diagnostic tool for the monitoring hepatic toxicity in patients with rheumatic disease undergoing methotrexate treatment.